Nostalgia As a Device for Dealing with Traumatic Experiences During the COVID-19 Crisis - Todorova, Bilyana; Padareva-Ilieva , Gergana (East European Journal of Psycholinguistics, 2021)
The paper is an investigation of nostalgia in its diverse manifestations in social media, mainly Facebook, during COVID-19 crisis in Bulgaria and is based on pre-observation which shows that communication through social media at that period was largely nostalgic. The study considers nostalgia as a strategy for dealing with the 2020 state of emergency during which the lack of physical contact and social experiences can create preconditions for anxiety, depression and fear leading to traumatic consequences. The research is based on empirical material actively collected using the method of the included observation in the period from the 15th of March 2020, when the state of emergency in connection with COVID-19 was declared in Bulgaria, until the 30th of June 2020. The purpose of the paper is to present the nostalgic modes in Facebook and to reveal the reasons for their success as communicative and social messages. Applying interdisciplinary and multimodal approach the study describes the nostalgic manifestations by classifying thematically the initiatives, communication strategies and topics, oriented towards the past, as well as revealing their meaning for the society. The results show that the main role of nostalgic Facebook modes is to unite people in times of isolation, to raise their spirit and thus save them from the traumas that the COVID-19 crisis can cause. The multimodal analysis of the Facebook images from the empirical data confirms that social media and modern technologies make it possible to create `new products` based on old stories or memories that acquire a new meaning in the specific COVID-19 situation, modelled by the culture and mentality of Bulgarians in isolation.